Синтез модели знаний и обучения индивидуума - Евсеева, И. В.; Петров, Э. Г. (УАДО, 2004)
The approach to identification of model of knowledge and training of an individual is considered. At identification of model two approaches are used: introspective and extrospective. The generalized model of behavior trained is offered
Keywords: обучение индивидуума